Marketing strategies for higher education institutions technological considerations and practices - Tripathi, Purnendu, 1975-; Mukerji, Siran; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"Marketing Strategies for Higher Education Institutions: Technological Considerations and Practices provides different aspects of marketing management and technological innovations in all parts of education, including K-12, non-formal, and distance education"--Provided by publisher.
What is the secret of successful university brands? / Chris Chapleo -- Marketing educational programs through technology and the right philosophies / Victor C. X. Wang -- Business lessons for higher education marketing / Ruth Gannon Cook, Kathryn Ley -- Identifying the basis for segmenting higher education: evidence from Egypt / Maha Mourad, Hamed M. Shamma -- A mobile market: opportunities and strategies in higher education / Thomas J. Hayes, Mary M. Walker -- Mediating effects of study outcomes on student experience and loyalty: a comparison of home and international students / Vanessa Ann Quintal, Tekle Shanka, Pattamaporn Chuanuwatanakul -- They're here, now how do you keep them?: lessons learned with first year college students / Ruth Gannon Cook -- How technologies can localize learners in multicultural space: a newly developed "global studies" curriculum / Gilbert Ahamer -- Higher education marketing: a study on the impact of social media on study selection and university choice / Efthymios Constantinides, Marc C. Zinck Stagno -- Using social network sites for higher education marketing and recruitment / Natalia Rekhter -- The Use of Facebook as a marketing tool by private educational institutions in Singapore / H. K. Leng -- Marketing to and developing faculty members to create high quality, highly interactive online courses / Jace Hargis -- Increasing graduate education relevance through innovative marketing: interview with Mike Scorzo / Lynn Wilson -- E-service delivery in higher education: meeting MBA student expectations / Matt Elbeck, Brian A. Vander Schee -- Technology in marketing education: insights from sales training / Eileen Bridges -- Service recovery encounters in the classroom: exploring the attributes of professors desired by male and female students / Sneha Chandra, Thorsten Gruber, Anthony Lowrie -- You name it: comparing holistic and analytical rating methods of eliciting preferences in naming an online program using ranks as a concurrent validity criterion / Michael J. Roszkowski, Scott Spreat -- Co-constructing a learning community: a tool for developing international understanding / Chris Robertson -- Assessing learning via Web 2.0 technologies: a dichotomy / Victor C. X. Wang, Beth Kania-Gosche -- Lighting the fires of entrepreneurialism?: constructions of meaning in an English inner city academy / Philip A. Woods, Glenys J. Woods.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed April 17, 2013).
Keywords: Education, Higher -- Marketing; Education, Higher -- Marketing -- Technological innovations; Digital service and education; Direct marketing for educational programs; E-marketing; Educational marketing research; Green marketing for education; Web 2.0 technologies and educational marketing; Electronic books